Effective management of print media (Herald of Journalism, 2020)
This article discusses the factors of affecting the efficiency of the news paper. Design plays an important role in the dissemination of the publica tion. The author considers such factors as the efficiency of the manage ment of the newspaper as the composition, the marketing policy oand the staff personal.
Keywords: newspaper, management, design, composition.